Current trends in Zika vaccine development - Francisco A. Lagunas-Rangel; Martha E. Viveros-Sandoval; Arturo Reyes-Sandoval (Elsevier, 2017)
The Zika virus (ZIKV) was first isolated in 1947 in Uganda. While it took 60 years for this virus to cause major outbreaks, an important shift in its ability to cause epidemics took place in the first and second decades of the this century: in 2007 in Yap Island, Micronesia, followed by French Polynesia in 2013 and, finally in 2015 and 2016, when ZIKV infections occurred throughout South America, Central America and the Caribbean, spreading rapidly to reach North America in just a single year. No licensed prophylactic vaccine is yet available but recent efforts towards the development of a vaccine have been remarkable from both the private and public sectors and include new candidate vaccines ranging from the classical live-attenuated or inactivated vaccines to more sophisticated approaches such as mRNA or genetically engineered viral platforms. Previous successes with licensed flavivirus vaccines indicate that a protective ZIKV vaccine should be an achievable goal. Nevertheless, numerous pre- and post-licensure challenges need to be taken into account, such as the interaction of vaccine-induced immune responses with other flaviviruses, in particular with dengue, where antibody-dependent enhancement could become an issue, and the importance of a rapid induction of protective responses during pregnancy.